Scientific truth or debate: On the link between perceived scientific consensus and belief in anthropogenic climate change. (October 2019) - Bertoldo, Raquel; Mays, Claire; Böhm, Gisela; Poortinga, Wouter; Poumadère, Marc; Tvinnereim, Endre; Arnold, Annika; Steentjes, Katharine; Pidgeon, Nick
Scientists overwhelmingly agree that climate change exists and is caused by human activity. It has been argued that communicating the consensus can counter climate scepticism, given that perceived scientific consensus is a major factor predicting public belief that climate change is anthropogenic. However, individuals may hold different models of science, potentially affecting their interpretation of scientific consensus. Using representative surveys in the United Kingdom, France, Germany and Norway, we assessed whether the relationship between perceived scientific consensus and belief in anthropogenic climate change is conditioned by a person's viewing science as 'the search for truth' or as 'debate'. Results show that perceived scientific consensus is higher among climate change believers and moreover, significantly predicts belief in anthropogenic climate change. This relationship is stronger among people holding a model of science as the 'search for truth'. These results help to disentangle the effect of implicit epistemological assumptions underlying the public understanding of the climate change debate.